Size-Activity Relationship of TiO2-Supported Pt Nanoparticles in Hydrogenation Reactions - Qi Zhang; Tianbo Li; Xiang-Ting Min; Shu-Xian Li; Xunzhu Jiang; Qian Zhang; Yangyang Li; Xinlong Yan; Rui Feng; Feifei Yang; Wei Zhou; Xiaoyan Hu; et al. (Inorganics, 2025)
Quantitative assessments of the geometric influence on catalytic activity are crucial for catalyst design and understanding reaction mechanisms. In this study, we synthesized a series of catalysts comprising TiO2-supported Pt nanoparticles with varying particle sizes, which were systematically evaluated in representative hydrogenation reactions. A consistent size–activity relationship is established, wherein overall turnover frequency (TOF) values (TOFoverall: calculated as moles of reactant converted per mole of Pt per hour) are modeled as functions of the average diameter of the supported Pt particles, yielding slope values consistently near −1 across a variety of common substrates. This finding underscores that catalytic activity predominantly originates from surface sites on the Pt nanoparticles rather than from interfacial, edge, or corner active sites.